Helen Bonny - Kenny, Carolyn; Hesser, Barbara (Voices: A World Forum for Music Therapy, 2010)
... in the midst of the regret, we all felt a tremendous sense of gratitude that we had known Helen Bonny and shared the many benefits of her work especially in the development of The Bonny Method of Guided Imagery and Music (GIM).